Critical Factors Affecting Cost and Time Overrun of Construction Projects in Pakistan - Samiullah Sohu,; Tahara Ramadzan Md Kassim,; Najamuddin Sohu,; Karthikeyan Loganathan, (International Journal of Sustainable Construction Engineering and Technology, 2024)
Construction industry plays a vital role in Pakistan’s economic development. However, the success of construction projects is significantly influenced by well-structured plans and timelines. This study aims to explore the critical factors affecting the cost and duration of construction projects in Pakistan. To identify these factors, an in-depth literature review was conducted, followed by the Delphi technique, where a series of questionnaires were distributed to industry experts. Multiple rounds of surveys were carried out with professionals, including consultants, contractors, and clients. The collected responses were analysed and ranked using the Relative Importance Index (RII) method. The findings revealed several key contributors to time overruns, such as material selection, changes in material types and specifications during construction, poor equipment maintenance, shortages of construction materials, financial disputes between owners and contractors, and labour shortages. Similarly, major causes of cost overruns were identified, including inflation and rising material prices, inappropriate construction methods, project modifications by owners, frequent equipment breakdowns, and rework due to construction errors. Understanding these factors is crucial for improving project planning and execution, ultimately enhancing the efficiency of Pakistan’s construction industry.